The Influence of Audit Policies on Performance Audit in Oil and Gas Sector in Tanzania - MBOGELLA, AMANI; Hatib, Semboja; Abdallah, Zuhura (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2023)
In recent years Tanzania has undergone various reforms such as extractive industry reforms and financial management reforms. This is due to dissatisfaction with the management of public resources, particularly in the oil and gas sector. One of the key elements of these overall reforms in the public sector is the financial control mechanisms particularly on the performance audit, unlike the regularity audit which looks at individual transactions to determine if the transaction conforms to the authority and complies with expenditure rules and related funding institutions. In order to select a broad range of participants who are information-rich, an intensity and maximum variation sampling procedure were used. Primary and secondary data were collected whereby structured questionnaires, focused group discussion, and interview methods were employed under the study. The overall results indicate that on average most of the respondents disagreed that value for money is placed on auditing the oil and gas sector in Tanzania. Audit policies had a positive influence on performance audits,s particularly in the oil and gas sector. This implied that a unit change in audit policy will positively increase performance in the oil and gas sector in Tanzania's economy by the rate of 0.221. Furthermore, an effective Performance audit will increase accountability in the oil and gas sector. Hence the value of this study is paramount. Keywords: Audit policy, Performance Audit; Oil and gas sector; Tanzania